2015
DOI: 10.1186/s13395-015-0046-6
|View full text |Cite
|
Sign up to set email alerts
|

Developmental myosins: expression patterns and functional significance

Abstract: Developing skeletal muscles express unique myosin isoforms, including embryonic and neonatal myosin heavy chains, coded by the myosin heavy chain 3 (MYH3) and MYH8 genes, respectively, and myosin light chain 1 embryonic/atrial, encoded by the myosin light chain 4 (MYL4) gene. These myosin isoforms are transiently expressed during embryonic and fetal development and disappear shortly after birth when adult fast and slow myosins become prevalent. However, developmental myosins persist throughout adult stages in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
388
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 411 publications
(421 citation statements)
references
References 111 publications
(145 reference statements)
29
388
1
3
Order By: Relevance
“…The developmental marker eMHC is expressed in newly forming myofibers (44,45). Consistent with this, we observed that it was strongly expressed in regenerating control and Pak1 Ϫ/Ϫ muscle at D5PI, with a slight reduction in Pak2 cKO mice (Fig.…”
Section: Resultssupporting
confidence: 86%
“…The developmental marker eMHC is expressed in newly forming myofibers (44,45). Consistent with this, we observed that it was strongly expressed in regenerating control and Pak1 Ϫ/Ϫ muscle at D5PI, with a slight reduction in Pak2 cKO mice (Fig.…”
Section: Resultssupporting
confidence: 86%
“…To test whether ectopic TGF-β signaling inhibited hPSC-SMPCs from forming more mature myotubes, we measured embryonic (MYH3), fetal (MYH8), and adult (MYH1) myosins at both the RNA and protein levels 40 . We found without TGF-βi, hPSC-myotubes predominately expressed embryonic and fetal myosins.…”
Section: Resultsmentioning
confidence: 99%
“…In human fast-twitch muscle, MHC-IIb is present only in a very small subset of specialized muscle, but is observed to re-activate in limb muscle undergoing regeneration after profound degeneration (242). As seen in cardiac muscle, re-expression of fetal myosins occurs in regenerating muscle and during disease (e.g., hypothyroidism) [reviewed in (610)].…”
Section: Sarcomere—the Basic Contractile Unit Of Striated Musclementioning
confidence: 99%